Automatic generation control of multi-area interconnected power systems using ANN controller - Alzaareer K.; Al-Shetwi A.Q.; El-Bayeh C.Z.; Taha M.B. (International Information and Engineering Technology Association, 2023)
Electric load flow; Electric power system interconnection; Neural networks; Three term control systems; Area control error; Artificial neural network controllers; Automatic generation control; MATLAB /simulink; PI Controller; PID controllers; Tie line; Controllers